PENGARUH KEMIRINGAN LERENG TERHADAP KUALITAS TANAH PADA PERTANAMAN NILAM DI KECAMATAN WOLASI, KABUPATEN KONAWE SELATAN - Suleman, Darwis; Alam, Syamsu; Rustam, La Ode; Yusuf, Dewi Nurhayati (Agriculture Faculty of Flores University, 2025)
The slope gradient is one of the critical factors influencing soil functions through erosion, transportation and soil sedimentation. The general objective of this study was to evaluate the change of soil quality at different slopes gradient and specifically to prepare a soil quality data base as a reference for making sustainable land use policies. This study used a systematic free survey method in which the sample points were determined purposively based on the slope gradient, namely 0-8% and 8-15%. Three sample points were set up at each slope gradient comprising 4 subsamples each and then composited, so that 9 composite samples were obtained. Soil properties observed include texture, pH, organic C, total N, available P and K. The results highlighted that the soil organic C, total N and available K at 0-8% slope gradient increased by 88.25%, 29.87% and 10.53% respectively compared to the 8-15% slope gradient. The Soil Quality Index (SQI) at 0-8% and 8-15% slopes gradient was recorded by 0.70 (good) and 0.60 (moderate), respectively. It was observed a decline in organic C and total N as well as available K with an increasing of slope gradient. Therefore, it is highly recommended to practice a conservation planting system to avoid a decline in soil quality in the future.